Rowdy Revolutions - Terry Deary (London Scholastic, 2011)
Readers can discover all the foul facts about Rowdy Revolutions, including which Chinese emperor was overthrown by his mum, why one revolution made ugly people very scared indeed and what Count Dracula was really like. With a bold, accessible new look and a heap of extra-horrible bits, these bestselling titles are sure to be a huge hit with yet another generation of Terry Deary fans.